2021
DOI: 10.3390/jcm10173780
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality in Patients over 90 Years of Age Following Posterior Stabilization for Acute Traumatic Odontoid Type II Fractures: A Retrospective Study with a Mean Follow-Up of Three Years

Abstract: Odontoid type II fractures represent the most common cervical spine injuries in the elderly. The decision for surgical treatment in very elderly patients is still controversial. The aim of this study was to assess morbidity and mortality in patients over 90 years of age undergoing CT-guided posterior stabilization for unstable odontoid type II fractures. A total of 15 patients with an acute traumatic odontoid type II fracture who received surgical treatment for unstable odontoid type II fractures were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Cardiac disease (44.3%), renal disease (37.1%), and psychiatric disease (37.1%) were signi cantly more frequent among the elderly than among the young. Issa et al studied patients ≥ 90 years old with traumatic dentate fractures and found that they had a greater frequency of comorbidities involving vital organs, including heart failure (40%), diabetes mellitus (27%), peripheral vascular disease (27%), and myocardial infarction (20%) [13]. The present study examined patients ≥90 years old, nding comorbidities in 89.7%.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Cardiac disease (44.3%), renal disease (37.1%), and psychiatric disease (37.1%) were signi cantly more frequent among the elderly than among the young. Issa et al studied patients ≥ 90 years old with traumatic dentate fractures and found that they had a greater frequency of comorbidities involving vital organs, including heart failure (40%), diabetes mellitus (27%), peripheral vascular disease (27%), and myocardial infarction (20%) [13]. The present study examined patients ≥90 years old, nding comorbidities in 89.7%.…”
Section: Discussionmentioning
confidence: 69%
“…Elderly individuals are more likely to have comorbidities such as cardiovascular, pulmonary, and renal diseases than younger people, and are considered at high risk for postoperative complications [12][13][14]. Ghanem et al studied 71 patients ≥ 90 years old with pertrochanteric fracture [12].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac disease (44.3%), renal disease (37.1%), and psychiatric disease (37.1%) were significantly more frequent among the elderly than among younger patients. Issa et al studied patients over 90 years old with traumatic dentate fractures and found that they had a greater frequency of comorbidities involving vital organs, including heart failure (40%), diabetes mellitus (27%), peripheral vascular disease (27%), and myocardial infarction (20%) [ 13 ]. The present study examined patients ≥90 years old, finding comorbidities in 89.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spine fractures are associated with high morbidity and mortality rates in the geriatric population (22)(23)(24). Odontoid fractures are highly prevalent among the elderly.…”
Section: Discussionmentioning
confidence: 99%